Epigenetic Regulation of the Ontogenic Expression of the Dopamine Transporter - Green, Ashley L.; Eid, Aseel; Zhan, Le; Zarbl, Helmut; Guo, Grace L.; Richardson, Jason R. (Frontiers in Genetics, 2019)
The dopamine transporter (DAT) is a plasma membrane transport protein responsible for regulating the duration and intensity of dopaminergic signaling. Altered expression of DAT is linked to neurodevelopmental disorders, including attention deficit hyperactivity disorder and autism spectrum disorder, and is shown to contribute to the response of psychotropic drugs and neurotoxicants. Although the postnatal levels of DAT have been characterized, there are few data regarding the mechanisms that regulate postnatal DAT expression. Here, we examine the ontogeny of DAT mRNA from postnatal days 0 to 182 in the rat brain and define a role for epigenetic mechanisms regulating DAT expression. DAT mRNA and protein significantly increased between PND 0 and 6 months in rat midbrain and striatum, respectively. The epigenetic modifiers Dnmt1, Dnmt3a, Dnmt3b and Hdac2 demonstrated age associated decreases in mRNA expression whereas Hdac5 and Hdac8 showed increased mRNA expression with age. Chromatin immunoprecipitation studies revealed increased protein enrichment of acetylated histone 3 at lysines 9 and 14 and the dopaminergic transcription factors Nurr1 and Pitx3 within the DAT promoter in an age-related manner. Together these studies provide evidence for the role of epigenetic modifications in the regulation of DAT during development. The identification of these mechanisms may contribute to potential therapeutic interventions aimed at neurodevelopmental disorders of the dopaminergic system.